Functionality of lactic acid bacteria peptidase activities in the hydrolysis of gliadin-like fragments - Gerez, Carla Luciana (2008)
Aims: To evaluate the role of the peptidase activities from sourdough lactic acid bacteria (LAB) in the degradation of α-gliadin fragments. Methods and Results: Different proline-containing substrates were hydrolysed by LAB indicating pro-specific peptidase activities. Lactobacillus plantarum CRL 775 and Pediococcus pentosaceus CRL 792 displayed the highest tri- and di-peptidase activities, respectively. Lactobacillus plantarum strains hydrolysed more than 60%α-gliadin fragments corresponding to the 31-43 and 62-75 amino acids in the protein after 2 h. None of the LAB strains alone could hydrolyse 57-89 α-gliadin peptide; however, the combination of L. plantarum CRL 775 and P. pentosaceus CRL 792 led to hydrolysis (57%) of this peptide in 8 h. Conclusions: The capacity of LAB strains to degrade α-gliadin fragments was not correlated to individual peptidase activities. Several strains separately degraded the 31-43 and 62-75 α-gliadin fragments, while the 57-89 peptide degradation was associated with the combination of peptidase profiles from pooled LAB strains. This is the first report on the peptide hydrolase system of sourdough pediococci and its ability to reduce α-gliadin fragments. Significance and Impact of the Study: This study contributes to a better knowledge of sourdough LAB proteolytic system and its role in the degradation of proline-rich α-gliadin peptides involved in celiac disease. © 2008 The Authors.